Ecotourism and Protected Areas Sustainable Financing: A Case Study of Wadi El Gemal Visitor Center - Tawfik, Rady; Sarhan, Mahmoud (Journal of Tourism, Sustainability and Well-being, 2021)
Ecotourism has the potential to support protected areas (PAs) financing where PAs’ visitor centers (VCs) are mechanisms for raising public awareness, and revenue generation. Park agencies must shift from a sole emphasis on preservation to include management approaches that increase the benefits of ecotourism and promote partnerships, collaboration, and integration of tourist activities into protected areas core business. A strategy is needed for Wadi El Gemal National Park (WGNP) to enhance tourism practices in a manner that will protect ecosystems, benefit the local community, and promote sustainability. Visitor centers contribution to the development and sustainability of PAs and ecotourism is rarely investigated. This article sheds the light on PAs’ visitor centers and their role in ecotourism, conservation, and PAs financial sustainability. It defines the potential ecotourism products and services in WGNP and its Visitor Center, elucidates the impacts of COVID-19 on the park and the local community, and identifies the necessary tools and resources to implement a sustainable business and management model for WGNP Visitor Center. The results of the VC’s probability analysis and the financial indicators suggest that the Visitor Center is financially feasible and could present a model of sustainable revenue generation and ecotourism development in WGNP.